Analysis of Organizational Commitment, Training, and Compensation on Job Satisfaction in Career Mediation at Sea Freight Forwarding Companies - Aswanti Setyawati; Rohana Sitanggang; Lira Agusinta; Primadi Candra Susanto; Esterlinus Edwin Lermatan (Dinasti Publisher, 2025)
This study aims to analyze the effect of Organizational Commitment, Training, and Compensation on Job Satisfaction mediated by Career Path in Sea Freight Forwarding Companies. The method used is descriptive-qualitative, with a literature review approach. This study synthesizes findings from various relevant internationally indexed academic articles. Data were collected from reputable internationally indexed articles obtained through databases such as Scopus, Web of Science, Emerald, Springer, and Google Scholar. The selected literature was analyzed using reduction techniques, data presentation in matrix form, and comparative synthesis to find patterns, similarities, and differences between studies. The results of the study indicate that Organizational Commitment, Training, and Compensation affect Job Satisfaction, either directly or indirectly through career paths. The contribution of this research is that it provides significant theoretical and practical contributions in the field of human resource management, particularly in the shipping and logistics sector. The novelty of this research lies in integrating a career path mediation model in analyzing the relationship between organizational commitment, training, and compensation on job satisfaction in the specific context of sea freight forwarding companies in Indonesia, which has not been widely studied in academic literature.